Clergy and the Care of the Insane in Eighteenth-Century Britain - Houston, R. A. (Church history, 2004)
Writers on seventeenth- and eighteenth-century England have stressed the significance of doctors and clergy in the provision of residential care for the better-off mad person. “The private madhouse trade in fact started with the practice of doctors taking private patients into their homes.” So wrote Macalpine and Hunter. According to William Parry-Jones, English “lunatics from the more affluent classes were cared for individually, often in the custody of medical men or clergymen.” The two professions commonly overlapped, meaning that clerics could provide medical care. Andrew Mason has written enthusiastically that “towards the end of the seventeenth-century, so-called ‘clerical mad doctors’ abounded.” As educated men working in an occupation with few barriers to entry, English clergy could “readily take up medicine,” which was just one element of the burgeoning eighteenth-century market place. “Those entering the madbusiness were drawn from … clergymen, both orthodox and non-conformist, businessmen, widows, surgeons, speculators, and physicians.”